Single-nucleus RNA-seq and FISH identify coordinated transcriptional activity in mammalian myofibers - Matthieu Dos Santos (Nature Portfolio, 2020)
Whether skeletal muscle fibre gene expression is coordinated as a whole in different nuclei in the fibre is unclear. Here, the authors use single nucleus RNAseq and ATACseq to show the transcriptome heterogeneity of muscle nuclei in the adult mouse fibre, with correlations between the two datasets.